Advancing crop disease resistance through genome editing: a promising approach for enhancing agricultural production - Manzoor, Subaya; Nabi, Sajad Un; Rather, Tariq Rasool; Gani, Gousia; Mir, Zahoor Ahmad; Wani, Ab Waheed; Ali, Sajad; Tyagi, Anshika; Manzar, Nazia (Frontiers in Genome Editing, 2024)
Modern agriculture has encountered several challenges in achieving constant crop yield stability especially due to disease outbreaks and lack of long-term disease-resistant crop cultivars. In the past, disease outbreaks in economically important crops had a major impact on food security and the economy. In the future, climate-driven emergence of new pathovars or changes in their host specificity further poses a serious threat to sustainable agriculture. At present, chemical-based control strategies are frequently used to control microbial pathogens , doing so comes with hazards to other living things and has resulted in the creation of resistant phyto-pathogens. As a replacement, cultivating engineered disease-resistant crop cultivars can help to minimize the negative impact of regular pesticides on agriculture and the environment. Although traditional breeding and genetic engineering have been instrumental in crop disease improvement but have certain limitations such as labour intensity, time consumption, and low efficiency. In this regard, genome editing has emerged as one of the potential tools for improving disease resistance in crops by targeting multiple traits with more accuracy and efficiency. For instance, genome editing techniques, such as CRISPR/Cas9, CRISPR/Cas13, base editing, TALENs, ZFNs, and meganucleases, have proved successful in improving disease resistance in crops through targeted mutagenesis, gene knockouts, knockdowns, modifications, and activation of target genes. CRISPR/Cas9 is unique among these techniques because of its remarkable efficacy, low risk of off-target repercussions, and ease of use. Some primary targets for developing CRISPR-mediated disease-resistant crops are host-susceptibility genes (the S gene method), resistance genes (R genes) and pathogen genetic material that prevents their development, broad-spectrum disease resistance. The use of genome editing methods has the potential to notably ameliorate crop disease resistance and transform agricultural practices in the future. This review highlights the impact of phytopathogens on agricultural productivity. Next, we discussed the tools for improving disease resistance while focusing on genome editing. We provided an update on the accomplishments of genome editing, and its potential to improve crop disease resistance against bacterial, fungal and viral pathogens in different crop systems. Finally, we highlighted the future challenges of genome editing in different crop systems for enhancing disease resistance.